Brief Research Report: Quantitative Analysis of Potential Coronary Microvascular Disease in Suspected Long-COVID Syndrome - Doeblin, Patrick; Steinbeis, Fridolin; Scannell, Cian M.; Goetze, Collin; Al-Tabatabaee, Sarah; Erley, Jennifer; Faragli, Alessandro; Pröpper, Felix; Witzenrath, Martin; Zoller, Thomas; Stehning, Christian; Gerhardt, Holger; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Case series have reported persistent cardiopulmonary symptoms, often termed long-COVID- or post-COVID-Syndrome, in more than half of patients recovering from COVID-19. Recently, alterations in microvascular perfusion have been proposed as a possible pathomechanism in long-COVID-syndrome. We examined whether microvascular perfusion, measured by quantitative stress perfusion CMR, is impaired in patients with persistent cardiac symptoms post COVID-19. Methods Our population consisted of 33 patients post COVID-19 examined in Berlin and London, 11 (33%) of which complained of persistent chest pain and 13 (39%) of dyspnea. The scan protocol included standard cardiac imaging and a dual-sequence quantitative stress perfusion. Standard parameters were compared to 17 healthy controls from our institution. Quantitative perfusion was compared to published values of healthy controls. Results Stress MBF was significantly lower (31.8 ± 5.1 [µl/g/beat] vs. 37.8 ± 6.0 [µl/g/beat], P < .001) and T2 relaxation time was significantly higher (46.2 ± 3.6 ms vs. 42.7 ± 2.8 ms, P = .002) post COVID-19 compared to healthy controls. Stress MBF, T1 and T2 relaxation time were not correlated to COVID-19 severity (Spearman r = -.302, -.070 and -.297, respectively) or presence of symptoms. Stress MBF showed a U-shaped relation to time from PCR to MRI, no correlation to T1 relaxation time and a negative correlation to T2 relaxation time (Pearson r = -.446, P = .029). Conclusion While we found a significantly reduced microvascular perfusion post COVID-19 compared to healthy controls, this reduction was not related to symptoms and COVID-19 severity.